Developing Experimental Competency in Pre-Service Physics Teachers with An Inquiry-Based Approach - Nguyen, Thanh Loan; Nguyen, Van Bien; Tran, Ngoc Chat (Department of Physics, Faculty of Mathematics and Natural Sciences, 2024)
The study aims to show that an inquiry-based approach develops pre-service teachers' experimental competency. The static-group pretest-posttest design, an experimental quantitative analysis method, has been utilized. The experimental group comprised 36 pre-service physics teachers, with 11 participants in the control group. Assessment of experimental competency levels included the PLIC test and an experimental competency test. The experimental competency of pre-service teachers is evaluated through video recordings, observations, learning products, and surveys conducted via Microsoft Teams. Following each experiment, pre-service teachers assess their achievement levels based on behavioral indicators in a rubric table, utilizing a 3-level behavior scale for self and peer assessment. Parametric and nonparametric tests were chosen for evaluating the research data after confirming normal distribution using the Kolmogorov-Smirnov and Shapiro-Wilk tests (in the case of SPSS 20.0). The article’s main findings determined that an inquiry-based laboratory organizational procedure for each experiment in the General Physics Laboratory course to develop pre-service teachers' competency included two stages (stage 1 with six steps and stage 2 with four steps) under the pre-service teachers’ active self-discovery to perform learning tasks with three open levels of experiments. Within the scope of this article, we have given an illustrative example of applying this procedure for the experiment “Investigate the properties of collisions on an air track and verify the law of linear momentum conservation” in the General Physics Laboratory course for the second-year pre-service physics teachers. Furthermore, based on the test results along with survey findings and spider diagram analysis showed that this procedure developed relatively stable most of the behavioral indicators except for two behavioral indicators such as “Proposing ideas to improve experimental instruments” and “Proposed measures to reduce error” of pre-service physics teachers.